Adv
Deepak Bora
  • 0

Solve the following equation by using formula

  • 0
Share

Related Questions

Adv

1 Answer

  1. a(x²+1)= (a²+1)x

    ax² + a= (a²+1)x

    ax²-(a²+1)x+a=0

    Using the quadratic formula

    X= -b±√b²-4ac/2a

    X= -(-a²-1)±√[-(a²+1)]²-4.a.a /2a

    X= a²+1±√a ^4+1+2a²-4a² /2a

    X= a²+1±√a^4+1-2a² /2a

    X = a²+1±√(a²-1)² /2a

    X= a²+1± a²-1 /2a

    ∴x= a²+1+a²-1 /2a & x= a²+1-a²+1 /2a

    x =a, &  x= 1/a

     

    • 0
Leave an answer

Leave an answer

Browse

Choose from here the video type.

Put Video ID here: https://www.youtube.com/watch?v=sdUUx5FdySs Ex: "sdUUx5FdySs".

Captcha Click on image to update the captcha.